Availability of Lifesaving Maternal and Child Health Commodities and Associated Factors in Public and Private Health Facilities of Addis Ababa, Ethiopia. (28th November 2019) - Damtew, Dagim; Worku, Fikru; Tesfaye, Yonas; Jemal, Awol
Background: Inaccessible, unaffordable, and poor quality care are the key underlying reasons for the high burden of maternal and child morbidity and mortality in low- and middle-income countries. Objective: To assess the availability of lifesaving maternal and child health (MCH) commodities and associated factors in public and private health facilities of Addis Ababa, Ethiopia, 2016. Methods: Institutional-based, descriptive cross-sectional study was carried out in the selected health facilities (29 publics and 6 private) in Addis Ababa. The data were collected through pretested, structured questionnaire, and in-depth interviews. For the quantitative analysis, data were analyzed using SPSS version 20 statistical software, SPSS Inc. Descriptive statistics were used to summarize the variables, and the Spearman correlation test was run to determine the predictors of the outcome variables. For the qualitative data, the data were handled manually and transformed into categories related to the topics and coded on paper individually in order to identify themes and patterns for thematic analysis. Result: The overall availability of the lifesaving MCH commodities in the health facilities was 74.3%. There is a moderate, positive association between the availability of lifesaving MCH commodities with the adequacy of budget ( rs = 0.485, P < .001), use of more than 1 selection criteria during selection ( rs = 0.407, P = .015), and training given to health facilities on logistics management ( rs = 0.490, P = .003). Conclusion: The availability of the lifesaving MCH commodities in the health facilities was within the range of fairly high to high. Adequacy of budget, use of more than 1 selection criteria during selection, and training given on logistics management were the predictors of the availability of the commodities.